Applying a Wet-Type Grinder to Wheat Bran for Developing Breads - Thi Anh Le; Kazuyoshi Nakamura; Yuya Arai; Katsuyoshi Nishinari; Takao Nagano (Biology and Life Sciences Forum, 2021)
Despite being rich in dietary fibers, wheat bran is scarcely used as a food source because these dietary fibers have adverse effects on the texture. In this study, bran was atomized using a wet-type grinder (WG) to improve its physicochemical properties. The WG treatment improved the dispersion ability and viscosity of bran. Bread was then prepared by replacing 5% wheat flour with either WG-treated or WG-untreated bran. The WG-treated bread had a higher specific loaf volume and lower crumb hardness than the WG-untreated bran bread. The analysis of the enzymatic digestion of starch indicated a 20% decrease in rapidly digestible starch in WG-treated bran compared to untreated bran bread.